Concise history of mathematics - Struik, Dirk J. (New York Dover Publications, 1967)
This compact, well-written history - first published in 1948, and now in its fourth revised edition - describes the main trends in the development of all fields of mathematics from the first available records to the middle of the 20th century. Students, researchers, historians, specialists - in short, everyone with an interest in mathematics - will find it engrossing and stimulating.
Keywords: Mathematics essays; Mathematics; Mathematics reference